Aerodynamic drag study of speed skaters using CFD simulations - Wei, Y.; Wang, Y.; Nie, Y.; Weng, D.; Chen, L.; Ma, Y.; Pang, Z.; Wang, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
The aerodynamic drag of speed skaters was analyzed numerically at different posture angles of head, back and arm as well as team formation. Computational Fluid Dynamics (CFD) method was used to investigate the optimized posture of the skater and the drag law of the team formation. Detached Eddy Simulation (DES) was used as the numerical technique. CFD results showed that the drag area of the skater increased with the increasing angle of the head, back, and arms due to the increased high-pressure areas on the windward side and the increased low-pressure areas on the leeward side of the skater. CFD results also showed that all three skaters had lower drag area in the team pursuit competition compared with an isolated skater. The drag area of the latter two skaters was significantly smaller than that of the first skater, and the drag area of the foremost skater increased sharply when the axial spacing was more than 0.6 m. The drag area for all three skaters increased as the lateral offset increased. Moreover, the research in this paper presented an important reference for the drag reducing optimization of speed suits and helmets, and the method could be expanded to other sports.